High-temperature-resistant insulating flame-retardant powder coating and preparation method thereof
Patent Information
- Application Number
- CN202611210848.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种耐高温绝缘阻燃的粉末涂料及其制备方法,解决了现有粉末涂料在高温受热时存在成瓷层致密性不足、阻燃性差以及固化成膜过程中微量水汽残留导致绝缘性能下降的问题
1.本发明通过在配方中引入聚合型芳香族碳二亚胺与亲水型气相二氧化硅,利用碳二亚胺主链上的官能团消耗涂料体系中吸附的微量水分,从而降低了游离水汽对涂层电绝缘性能的干扰。该原位反应生成的极性聚脲基团进而与气相二氧化硅表面的游离硅羟基产生动态氢键交联,在聚合物熔体内构建出适宜的触变网络,改善了涂膜在高温受热状态下的流挂与滴落现象。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder coating technology, specifically to a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method. Background Technology
[0002] Powder coatings are widely used in electrical insulation, electronic component encapsulation, and high-voltage equipment surface protection due to their environmentally friendly, solvent-free characteristics. To meet the protection requirements of specific working conditions, these coatings must possess high-temperature resistance, electrical insulation, and flame-retardant properties. In existing formulation systems, epoxy resin is typically combined with heat-resistant resin as a composite matrix, with various inorganic flame retardants and mineral fillers added. The mixture is then processed into powder through conventional processes such as blending, extrusion, and pulverization, aiming to impart the corresponding basic physical and chemical protective properties to the substrate after curing.
[0003] During material blending, processing, storage, and transportation, the resin base and inorganic filler surfaces easily absorb trace amounts of moisture from the environment. This moisture is difficult to completely expel during the coating's melting, leveling, and high-temperature curing stages, leaving microscopic defects at the interface between the organic and inorganic phases, thus negatively interfering with the electrical insulation performance of the final coating. Simultaneously, conventional resin and flame retardant combinations, when subjected to thermal degradation induced by high-temperature flames, often fail to rapidly undergo in-situ sintering on the coating surface to form a continuous inorganic ceramic layer. The resulting loose residue has limited ability to block external heat penetration and the overflow of internal combustible gases, and it is also difficult to effectively suppress the sagging and dripping of polymer melt at high temperatures, leaving room for improvement in the overall flame retardant performance of the system.
[0004] Conventional powder coatings are typically prepared by mixing all components in a single process and feeding them into a twin-screw extruder. Because the curing catalyst comes into direct contact with the main resin at the initial stage of extrusion, under continuous heat conduction and mechanical shearing within the barrel, some materials are prone to premature cross-linking. This micro-gelation phenomenon not only reduces the initial fluidity of the system and hinders the uniform dispersion of inorganic fillers in the resin matrix, but also makes the coating prone to internal stress accumulation during later curing shrinkage, which is detrimental to maintaining the consistency of the product's macroscopic properties. Therefore, this invention provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method to address the shortcomings of existing technologies. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method, which solves the problems of insufficient density of the ceramic layer, poor flame retardancy, and decreased insulation performance due to trace amounts of water vapor residue during the curing process of existing powder coatings when heated at high temperatures.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a high-temperature resistant, insulating, and flame-retardant powder coating, which adopts the following technical solution: A high-temperature resistant, insulating, and flame-retardant powder coating, wherein the powder coating is made from raw materials comprising the following parts by weight: 40-60 parts of bisphenol A type solid epoxy resin; 10-20 parts of biphenyl type crystalline solid epoxy resin; 5-15 parts of solid methylphenyl polysiloxane resin; 15-25 parts of calcium hypophosphite; 10-20 parts of zinc borate; 5-15 parts of phlogopite powder; 2-6 parts of polymeric aromatic carbodiimide; 1-5 parts of hydrophilic fumed silica; 3-8 parts of amino pre-expanded modified layered bimetallic hydroxide; 0.5-1.5 parts of leveling agent; 0.2-1.0 parts of degassing agent; 2.0-5.0 parts of dicyandiamide; 0.1-0.5 parts of 2-methylimidazole; and 0.5-1.5 parts of catalyst masterbatch.
[0007] By adopting the above technical solution, this invention utilizes the physicochemical synergy between polymeric aromatic carbodiimide, hydrophilic fumed silica, and amino-pre-expanded modified layered bimetallic hydroxide to improve the insulation performance of the coating film while enhancing its ceramic flame-retardant effect under high-temperature heating. Specifically, during the coating melting and leveling stage, to address the phenomenon that trace amounts of moisture easily adsorbed on the surface of the resin matrix and filler, leading to interface defects, the polymeric aromatic carbodiimide introduced in the formulation has -N=C=N- functional groups on its main chain that can undergo a hydration addition reaction with moisture in the system. The chemical reaction formula is as follows: -N=C=N-+H2O→-NH-CO-NH-; This in-situ reaction consumes free water within the system, thereby mitigating the negative impact of trace amounts of water vapor on the final coating's electrical insulation performance. Simultaneously, the polar polyurea groups generated by this reaction (i.e., the -NH-CO-NH- structure) form hydrogen bonds with the free silanol groups on the surface of the hydrophilic fumed silica in the formulation. These dynamic hydrogen-bonded crosslinking sites distributed within the polymer construct a thixotropic network, allowing the network to reversibly disintegrate under shear stress to maintain flowability, while tending to reconstruct under static or heated conditions, thus inhibiting, to some extent, the thermal dripping of the melt.
[0008] When exposed to high-temperature environments, amino-pre-expanded modified layered bimetallic hydroxides exert multiple barrier effects. Due to the surface modification with aminosilane coupling agents, improved compatibility allows the layered structure to be better exfoliated and dispersed in the curing system, forming a physical barrier that delays charge and heat transfer. When exposed to high-temperature flames that trigger resin degradation, the layered structure dehydrates and collapses, generating nanoscale magnesium-aluminum spinel microcrystals. These microcrystals then sinter with silica in the system, as well as polyphosphate flux produced by the thermal decomposition of calcium hypophosphite and zinc borate, promoting the formation of a relatively continuous inorganic ceramic layer on the coating surface. This carbon-ceramic composite structure not only seals off some of the outflow channels of combustible gases but also impedes the inward penetration of external heat flow. By altering the thermal degradation path of the underlying polymer, this ultimately results in an improvement in the system's limiting oxygen index and vertical combustion rating.
[0009] Preferably, the bisphenol A type solid epoxy resin is end-capped with epoxy groups, has an epoxy equivalent of 700-900 g / eq, and a softening point of 85-95°C; the biphenyl type crystalline solid epoxy resin is 3,3',5,5'-tetramethyl-4,4'-biphenyl diglycidyl ether, has an epoxy equivalent of 180-200 g / eq, a crystallization melting point of 100-110°C, and a melt viscosity of less than or equal to 0.05 Pa·s at 120°C; the solid methylphenyl polysiloxane resin is a cross-linked organosilicon resin with Si-O-Si bonds as the backbone and phenyl and methyl side groups, has a silanol mass fraction of 2%-6%, and a softening point of 90-105°C.
[0010] By employing the above technical solution, in the blend matrix composed of these three specific resins, the bisphenol A structure primarily provides the basic film formation and adhesion, the rigid biphenyl skeleton helps maintain the mechanical strength of the cured product under high-temperature conditions, and the polysiloxane provides corresponding heat resistance. During the curing stage, the three components intertwine to form an interpenetrating cross-linked network, thereby enhancing the structural stability of the coating when facing thermal shock.
[0011] Preferably, the polymeric aromatic carbodiimide is a high molecular weight polymer containing -N=C=N- functional groups and sterically hindered aryl structures in its main chain repeating unit, with a residual isocyanate group mass fraction of less than or equal to 0.1% and a softening point of 70–90°C; the hydrophilic fumed silica is an amorphous fumed silica nanoparticle without surface hydrophobication treatment, with a specific surface area of 200–300 m² / g; the leveling agent is a polyacrylate copolymer with a weight-average molecular weight range of 3000–10000, formed by the physical adsorption of 65% polyacrylate onto a 35% fumed silica carrier.
[0012] By adopting the above technical solution, carbodiimide with a sterically hindered aryl structure and low isocyanate residue reduces the probability of side reactions with the resin in the early stage of processing. Meanwhile, the large specific surface area of hydrophilic silica with abundant free silanol groups provides a foundation for the formation of a high-density hydrogen bond network of polyurea groups, which is beneficial for maintaining the thixotropic state of the system during the reaction process.
[0013] Preferably, the amino-pre-expanded modified layered bimetallic hydroxide is prepared by a method comprising the following steps: dissolving magnesium nitrate hexahydrate and aluminum nitrate nonahydrate in deionized water at a magnesium ion to aluminum ion molar ratio of 2:1 to 3:1 to prepare a mixed salt solution; adding the mixed salt solution dropwise to an alkaline precipitate containing sodium hydroxide and sodium carbonate, maintaining the pH of the system at 9.5 to 10.0, and aging at 70 to 90°C for 12 to 24 hours, followed by washing and drying to obtain the original powder; dispersing the original powder in a mixed solvent of anhydrous ethanol and water at a volume ratio of 9:1, adding 5% to 10% by mass of 3-aminopropyltriethoxysilane, and refluxing at 70 to 90°C for 6 to 8 hours, followed by separation and drying to obtain the amino-pre-expanded modified layered bimetallic hydroxide.
[0014] By employing the above technical solution, 3-aminopropyltriethoxysilane expands the interlayer spacing of layered bimetallic hydroxides while grafting amino functional groups onto the powder surface. This modification reduces the polarity of the inorganic powder surface, promoting better dispersion uniformity in the organic resin phase and reducing the possibility of local insulation defects caused by inorganic particle agglomeration.
[0015] Preferably, the catalyst masterbatch is made by melt extrusion of the following raw materials in parts by weight: 20-80 parts of aluminum acetylacetonate; 200-500 parts of zinc stannate; and 300-500 parts of bisphenol A type solid epoxy resin.
[0016] By adopting the above technical solution, aluminum acetylacetonate and zinc stannate are pre-encapsulated and shaped with bisphenol A type epoxy resin, which limits the premature contact between the catalytic components and the main material in the front section of the extruder. This physical isolation achieves the corresponding slow-release delay effect, which helps to reduce the local gelation phenomenon of the material during the extrusion granulation process.
[0017] Secondly, the present invention provides a method for preparing a high-temperature resistant, insulating, and flame-retardant powder coating, employing the following technical solution: A method for preparing a high-temperature resistant, insulating, and flame-retardant powder coating includes the following steps: S1. Weigh the bisphenol A type solid epoxy resin, biphenyl type crystalline solid epoxy resin and solid methylphenyl polysiloxane resin according to the formula, and mix them to obtain material group A; S2. Weigh the following ingredients according to the formula: calcium hypophosphate, zinc borate, phlogopite powder, polymeric aromatic carbodiimide, hydrophilic fumed silica, amino pre-expanded modified layered bimetallic hydroxide, leveling agent, degassing agent, dicyandiamide, and 2-methylimidazole, and mix them to obtain material group B. S3. Add material group A and material group B together into a mixer and mix to obtain a premix; S4. The premixed material is continuously fed into the main feed port of the twin-screw extruder; at the same time, the catalyst masterbatch weighed according to the formula is independently and continuously fed into the twin-screw extruder through the side feeder. S5. Set the temperature step parameters and screw speed of the twin-screw extruder, and perform melt extrusion; S6. Press the extruded high-temperature melt into thin sheets, cool and shape it, and then crush it into sheet material; S7. The sheet material is fed into a pulverizer for pulverization, and the powder of the target particle size is collected by sieving to obtain the powder coating.
[0018] By adopting the above technical solution, the group mixing method initially improves the macroscopic homogeneity of the system. During the extrusion processing stage, the independent lateral feeding of the catalyst masterbatch establishes a spatiotemporally misaligned mixing mechanism: the main material in the front section of the extruder undergoes physical shearing in a low-viscosity state without the presence of a catalyst. This not only facilitates the delamination of the modified layered bimetallic hydroxide but also promotes the full wetting of the filler by the matrix; as the material progresses to the middle and rear sections of the extruder, the gradually melting catalyst masterbatch begins to participate in the solidification system. This misaligned processing technology reduces the local cross-linking phenomenon that is easily caused by traditional mixed extrusion and reduces the accumulation of internal stress at the phase interface during thermal shrinkage. This relatively uniform component distribution also helps reduce the generation of microcracks in the carbon-ceramic composite layer during the initial stage of combustion, thereby supporting the overall barrier performance of the coating against combustible gases.
[0019] Preferably, in step S4, the main feed port of the twin-screw extruder is located in zone 1 of the twin-screw extruder, and the side feeder is located in zone 3 of the twin-screw extruder; in step S5, the screw speed of the twin-screw extruder is controlled to be 300 rpm.
[0020] By adopting the above technical solution, the physical separation of the feeding section shortens the time the catalyst spends in the high-temperature barrel. The pre-plasticization and primary dispersion completed in the first two zones provide a relatively uniform medium environment for the introduction of the catalyst in the third zone, further suppressing premature cross-linking of the molten material.
[0021] Preferably, in step S5, the barrel operating temperature step parameters of the twin-screw extruder are set as follows: the first zone is kept at room temperature and water-cooled, the second zone has an operating temperature of 110-120°C, and the third zone to the die head has an operating temperature of 120-130°C.
[0022] By adopting the above technical solution, this gradient heating setting is adapted to the softening and reaction characteristics of the material. The ambient temperature water cooling in Zone 1 helps prevent powder agglomeration at the feed inlet, the heat provided in Zone 2 softens and melts the resin but has not yet triggered a violent reaction, and the temperature rise from Zone 3 to the die head accelerates the melting and dispersion of the catalyst masterbatch, ensuring that the material reaches the required degree of mixing before discharge.
[0023] Preferably, in step S7, the sheet material is fed into a pulverizer equipped with a water-cooling system for pulverization, the temperature of the pulverizing chamber is controlled to not exceed 30°C, and powder with a particle size D50 of 35-45 μm is collected after sieving and separation.
[0024] By adopting the above technical solution, the water cooling system can promptly remove the frictional heat generated by mechanical force, suppress the adhesion and agglomeration of the sheet material caused by local heating, and control the particle size distribution within a specific micron level, which is beneficial to improving the fluidization performance of the finished powder and the adhesion rate during subsequent electrostatic spraying.
[0025] Preferably, before performing step S4, the catalyst masterbatch is prepared as follows: aluminum acetylacetonate, zinc stannate, and bisphenol A type solid epoxy resin are mixed in a mixer to obtain a masterbatch premix; the masterbatch premix is fed into a twin-screw extruder, and the barrel operating temperature is set to 85-100°C for melt extrusion; after the extruded material is cooled and shaped, it is cut into particles with a diameter of 2-3 mm to obtain the catalyst masterbatch.
[0026] By adopting the above technical solution, the extrusion range of 85-100℃ is lower than the melting temperature of the subsequent main process. This reduces the risk of thermal deterioration during masterbatch preparation while shaping the catalytic components. The regular size of the granulated particles also facilitates more accurate continuous metering input by the side feeding system.
[0027] This invention provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method. It has the following beneficial effects: 1. This invention introduces polymeric aromatic carbodiimide and hydrophilic fumed silica into the formulation. The functional groups on the carbodiimide backbone consume trace amounts of adsorbed moisture in the coating system, thereby reducing the interference of free water vapor on the electrical insulation performance of the coating. The polar polyurea groups generated by this in-situ reaction then form dynamic hydrogen bonds with the free silanol groups on the surface of the fumed silica, constructing a suitable thixotropic network within the polymer melt and improving the sagging and dripping phenomena of the coating film under high-temperature heating conditions.
[0028] 2. This invention employs an amino-pre-expanded modified layered bimetallic hydroxide, combined with calcium hypophosphite and zinc borate to construct a flame-retardant system. The inorganic sheets modified with aminosilane surface achieve good exfoliation and dispersion in the resin matrix. When exposed to high-temperature flames, the magnesium aluminum spinel microcrystals generated by their dehydration and collapse sinter with the polyphosphate flux generated by the decomposition of phosphorus- and boron-containing additives, forming a relatively continuous inorganic carbon-ceramic composite layer in situ on the coating surface. This effectively blocks the inward penetration of external heat flow and the overflow of flammable gases from the underlying layer, thereby improving the overall flame-retardant rating of the coating.
[0029] 3. This invention establishes a spatiotemporal misalignment mixing mechanism by preparing a masterbatch by encapsulating the catalytic component in a bisphenol A-type solid epoxy resin carrier and combining it with a side-feeding process using a twin-screw extruder. This preparation process maintains the main formulation material in a low-viscosity, catalyst-free state in the front section of the extruder, promoting the physical dispersion and wetting of inorganic fillers. Introducing the catalytic masterbatch in the middle and rear sections of the extruder alleviates the premature cross-linking phenomenon that occurs when the material resides in the high-temperature barrel, reduces the accumulation of internal stress during curing, and supports the uniformity of the final coating's macroscopic properties. Attached Figure Description
[0030] Figure 1 This is a flowchart of the method of the present invention; Figure 2 The following is a comparison of the rheological properties of the powder coating of the present invention, wherein (a) is a trend diagram of the complex viscosity change at varying temperatures, and (b) is a trend diagram of the three-stage shear recovery change. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0033] The product identification CAS number of bisphenol A type solid epoxy resin is 25085-99-8. It is a linear oligomer formed by the condensation polymerization of bisphenol A and epichlorohydrin, with both ends capped by epoxy groups. The epoxy equivalent is 700-900 g / eq. It is solid at room temperature and has a softening point of 85-95℃.
[0034] The CAS number of the biphenyl-type crystalline solid epoxy resin is 85954-11-6, and its chemical name is 3,3',5,5'-tetramethyl-4,4'-biphenyl diglycidyl ether. It is a bifunctional crystalline epoxy resin with 3,3',5,5'-tetramethylbiphenyl as its backbone. The molecule contains glycidyl ether type epoxy groups at both ends. The epoxy equivalent is 180-200 g / eq. It is a highly crystalline solid powder at room temperature, with a crystallization melting point of 100-110℃ and a melt viscosity ≤0.05 Pa·s at 120℃.
[0035] Solid methylphenyl polysiloxane resin is a cross-linked organosilicon resin with Si-O-Si bonds as the backbone and phenyl and methyl side groups. It is a flaky solid powder at room temperature. The molecular structure retains uncondensed active free silanol groups, with a silanol mass fraction of 2% to 6% and a softening point of 90 to 105℃.
[0036] The polymeric aromatic carbodiimide used in this embodiment is a high molecular polymer containing -N=C=N- functional groups and sterically hindered aryl structures in the repeating unit of the macromolecular backbone. Its product specifications are ≤0.1% residual isocyanate group mass fraction, solid powder at room temperature, and softening point of 70-90℃.
[0037] The CAS number of the hydrophilic fumed silica is 112945-52-5. It is a native amorphous fumed silica nanoparticle that has not undergone surface hydrophobication treatment. It has a specific surface area of 200-300 m2 / g and contains free silanol groups on its surface.
[0038] The leveling agent is a polyacrylate copolymer with a weight-average molecular weight range of 3,000 to 10,000, which is formed by the physical adsorption of 65% polyacrylate onto a 35% fumed silica carrier.
[0039] The chemical name of the degassing agent is diphenylethanol ketone, CAS number 119-53-9, purity ≥99.0%, solid powder, melting point 133~137℃.
[0040] Aluminum acetylacetonate has the CAS number 13963-57-0 and is a crystalline powder at room temperature.
[0041] Zinc stannate has the CAS number 12036-37-2, is ahydrous, and has a particle size D50 ≤ 5 μm.
[0042] The CAS number for dicyandiamide is 461-58-5, with a purity of ≥99.5%, and it is a micro powder grade with a particle size D50 ≤5μm.
[0043] 2-Methylimidazole has the CAS number 693-98-1, a purity of ≥99.0%, and is a white crystalline powder at room temperature.
[0044] The CAS number for 3-aminopropyltriethoxysilane is 919-30-2, and its purity is ≥98.0%.
[0045] The CAS number for calcium hypophosphate is 7789-79-9. It is a micro powder grade with a particle size D50 ≤ 15 μm.
[0046] The CAS number for zinc borate is 1332-07-6. It is a micro powder with a particle size D50 ≤ 10 μm.
[0047] Phlogopite powder has the CAS number 12001-26-2. It is a layered silicate inorganic powder with a fineness of 600-1000 mesh and an aspect ratio ≥40.
[0048] The CAS number for magnesium nitrate hexahydrate is 13446-18-9, and its purity is ≥99.0%.
[0049] The CAS number for aluminum nitrate nonahydrate is 7784-27-2, and its purity is ≥99.0%.
[0050] The CAS number for sodium hydroxide is 1310-73-2, and its purity is ≥99.0%.
[0051] Sodium carbonate has a CAS number of 497-19-8 and a purity of ≥99.0%.
[0052] Preparation Example 1: This preparation example provides a method for preparing amino-pre-expanded modified layered bimetallic hydroxides, including the following steps: (1) Weigh magnesium nitrate hexahydrate and aluminum nitrate nonahydrate, dissolve them in deionized water at a ratio of magnesium ion to aluminum ion of 2.5 to 1, and prepare a mixed salt solution; separately prepare an alkaline precipitate containing sodium hydroxide and sodium carbonate; (2) The mixed salt solution was added dropwise to the alkaline precipitate under stirring. The pH of the system was maintained at 9.5 by adding dilute alkali solution. After the addition was completed, the slurry was transferred to a constant temperature reactor and crystallized and aged at 80°C for 18 hours. (3) The filter cake was filtered and washed with deionized water until neutral, then dried under vacuum at 80°C and ground to obtain the original powder. (4) The original powder was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and water in a volume ratio of 9:1. 3-aminopropyltriethoxysilane was slowly added dropwise at a mass of 7.5% of the original powder. The mixture was refluxed at 80°C for 7 h. After centrifugation and washing with anhydrous ethanol, the mixture was dried in a vacuum oven at 60°C for 12 h to obtain amino pre-expanded modified layered bimetallic hydroxide.
[0053] Preparation Example 2: This preparation example provides a method for preparing amino-pre-expanded modified layered bimetallic hydroxides, including the following steps: (1) Weigh magnesium nitrate hexahydrate and aluminum nitrate nonahydrate, dissolve them in deionized water at a ratio of 2:1 for magnesium ions to aluminum ions, and prepare a mixed salt solution; separately prepare an alkaline precipitate containing sodium hydroxide and sodium carbonate; (2) The mixed salt solution was added dropwise to the alkaline precipitate under stirring. The pH of the system was maintained at 9.5 by adding dilute alkali solution. After the addition was completed, the slurry was transferred to a constant temperature reactor and crystallized and aged at 70°C for 24 hours. (3) The filter cake was filtered and washed with deionized water until neutral, then dried under vacuum at 80°C and ground to obtain the original powder. (4) The original powder was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and water in a volume ratio of 9:1. 3-aminopropyltriethoxysilane, which was 5% of the mass of the original powder, was slowly added dropwise. The mixture was refluxed at 70°C for 8 hours, centrifuged and washed with anhydrous ethanol. The mixture was then dried in a vacuum oven at 60°C for 12 hours to obtain amino pre-expanded modified layered bimetallic hydroxide.
[0054] Preparation Example 3: This preparation example provides a method for preparing amino-pre-expanded modified layered bimetallic hydroxides, including the following steps: (1) Weigh magnesium nitrate hexahydrate and aluminum nitrate nonahydrate, dissolve them in deionized water at a ratio of 3:1 for magnesium ions to aluminum ions, and prepare a mixed salt solution; separately prepare an alkaline precipitate containing sodium hydroxide and sodium carbonate; (2) The mixed salt solution was added dropwise to the alkaline precipitate under stirring. The pH of the system was maintained at 10.0 by adding dilute alkali solution. After the addition was completed, the slurry was transferred to a constant temperature reactor and crystallized and aged at 90°C for 12 hours. (3) The filter cake was filtered and washed with deionized water until neutral, then dried under vacuum at 80°C and ground to obtain the original powder. (4) The original powder was ultrasonically dispersed in a mixed solvent of anhydrous ethanol and water in a volume ratio of 9:1. 3-aminopropyltriethoxysilane, with a mass of 10% of the original powder, was slowly added dropwise. The mixture was refluxed at 90°C for 6 hours, centrifuged and washed with anhydrous ethanol. The mixture was then dried in a vacuum chamber at 60°C for 12 hours to obtain amino pre-expanded modified layered bimetallic hydroxide.
[0055] Preparation Example 4: This preparation example provides a method for preparing catalyst masterbatch, including the following steps: (1) Weigh 50g of aluminum acetylacetonate, 350g of zinc stannate and 400g of bisphenol A type solid epoxy resin by weight, put them into a high-speed mixer and mix at 800rpm for 3min to obtain a premix. (2) Feed the premixed material into a micro twin-screw extruder with a length-to-diameter ratio of 30 and set the barrel working temperature to 95°C for melt extrusion; (3) After the material is extruded into strips by the die head, it enters the water tank for cooling and shaping, and is then cut into particles with a diameter of 2 to 3 mm by a pelletizer to obtain catalyst masterbatch.
[0056] Preparation Example 5: This preparation example provides a method for preparing catalyst masterbatch, including the following steps: (1) Weigh 80g of aluminum acetylacetonate, 500g of zinc stannate and 300g of bisphenol A type solid epoxy resin by weight, put them into a high-speed mixer and mix at 800rpm for 2min to obtain a premix. (2) Feed the premixed material into a micro twin-screw extruder with a length-to-diameter ratio of 30, and set the barrel working temperature to 100°C for melt extrusion; (3) After the material is extruded into strips by the die head, it enters the water tank for cooling and shaping, and is then cut into particles with a diameter of 2 to 3 mm by a pelletizer to obtain catalyst masterbatch.
[0057] Preparation Example 6: This preparation example provides a method for preparing catalyst masterbatch, including the following steps: (1) Weigh 20g aluminum acetylacetonate, 200g zinc stannate and 500g bisphenol A type solid epoxy resin by weight, put them into a high-speed mixer and mix at 800rpm for 4min to obtain a premix. (2) Feed the premixed material into a micro twin-screw extruder with a length-to-diameter ratio of 30 and set the barrel working temperature to 85°C for melt extrusion; (3) After the material is extruded into strips by the die head, it enters the water tank for cooling and shaping, and is then cut into particles with a diameter of 2 to 3 mm by a pelletizer to obtain catalyst masterbatch.
[0058] See Figure 1 Example 1: This embodiment provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method, including the following steps: (1) Weigh 50 kg of bisphenol A type solid epoxy resin, 15 kg of biphenyl type crystalline solid epoxy resin and 10 kg of solid methyl phenyl polysiloxane resin by weight, put them into a mixing tank and mix them to obtain material group A. (2) Weigh out 20 kg of calcium hypophosphate, 15 kg of zinc borate, 10 kg of phlogopite powder, 4 kg of polymeric aromatic carbodiimide, 3 kg of hydrophilic fumed silica, 5 kg of amino pre-expanded modified layered bimetallic hydroxide prepared in Preparation Example 1, 1.0 kg of leveling agent, 0.6 kg of degassing agent, 3.5 kg of dicyandiamide and 0.3 kg of 2-methylimidazole, and put them into a mixing tank for preliminary mixing to obtain material group B; (3) Put material group A and material group B into a high-speed mixer and mix at 800 rpm for 3 minutes to obtain a premix; (4) The premixed material is fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 40. The main feed port is located in the first zone of the extruder. At the same time, 1.0 kg of the catalyst masterbatch prepared in Preparation Example 4 is fed into the material group C independently and continuously through the side feeder located in the third zone of the extruder. (5) Set the temperature step parameters of the twin-screw extruder as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 is 115℃, Zone 3 to the die head is 125℃, and the screw speed is controlled at 300 rpm for asymmetric spatiotemporal gradient melt extrusion. (6) The extruded high-temperature melt is pressed into a sheet with a thickness of 1.5 mm by a pressing roller, and then cooled and shaped by a water-cooled fan before being crushed into small pieces by a crusher. (7) The sheet material is fed into an ACM micro pulverizer with an internal circulating water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. Then, the powder with a particle size D50 of 40μm is collected by cyclone separation and sieving to obtain the finished powder coating. Example
[0059] This embodiment provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method, including the following steps: (1) Weigh 40 kg of bisphenol A type solid epoxy resin, 10 kg of biphenyl type crystalline solid epoxy resin and 5 kg of solid methyl phenyl polysiloxane resin by weight, put them into a mixing tank and mix them to obtain material group A; (2) Weigh out 15 kg of calcium hypophosphate, 10 kg of zinc borate, 5 kg of phlogopite powder, 2 kg of polymeric aromatic carbodiimide, 1 kg of hydrophilic fumed silica, 3 kg of amino pre-expanded modified layered bimetallic hydroxide prepared in Preparation Example 2, 0.5 kg of leveling agent, 0.2 kg of degassing agent, 2.0 kg of dicyandiamide and 0.1 kg of 2-methylimidazole, and put them into a mixing tank for preliminary mixing to obtain material group B; (3) Put material group A and material group B into a high-speed mixer and mix at 800 rpm for 3 minutes to obtain a premix; (4) The premixed material is fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 40. The main feed port is located in the first zone of the extruder. At the same time, 0.5 kg of the catalyst masterbatch prepared in Preparation Example 6 is fed as material group C through the side feeder located in the third zone of the extruder. (5) Set the temperature step parameters of the twin-screw extruder as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 is 110℃, Zone 3 to the die head is 120℃, and the screw speed is controlled at 300 rpm for asymmetric spatiotemporal gradient melt extrusion. (6) The extruded high-temperature melt is pressed into a sheet with a thickness of 1.5 mm by a pressing roller, and then cooled and shaped by a water-cooled fan before being crushed into small pieces by a crusher. (7) The sheet material is fed into an ACM micro pulverizer with an internal circulating water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. Then, the powder with a particle size D50 of 35μm is collected by cyclone separation and sieving to obtain the finished powder coating. Example
[0060] This embodiment provides a high-temperature resistant, insulating, and flame-retardant powder coating and its preparation method, including the following steps: (1) Weigh 60 kg of bisphenol A type solid epoxy resin, 20 kg of biphenyl type crystalline solid epoxy resin and 15 kg of solid methyl phenyl polysiloxane resin by weight, put them into a mixing tank and mix them to obtain material group A; (2) Weigh out 25 kg of calcium hypophosphate, 20 kg of zinc borate, 15 kg of phlogopite powder, 6 kg of polymeric aromatic carbodiimide, 5 kg of hydrophilic fumed silica, 8 kg of amino pre-expanded modified layered bimetallic hydroxide prepared in Preparation Example 3, 1.5 kg of leveling agent, 1.0 kg of degassing agent, 5.0 kg of dicyandiamide and 0.5 kg of 2-methylimidazole, and put them into a mixing tank for preliminary mixing to obtain material group B; (3) Put material group A and material group B into a high-speed mixer and mix at 800 rpm for 3 minutes to obtain a premix; (4) The premixed material is fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 40. The main feed port is located in the first zone of the extruder. At the same time, 1.5 kg of the catalyst masterbatch prepared in Preparation Example 5 is fed as material group C through the side feeder located in the third zone of the extruder. (5) Set the temperature step parameters of the twin-screw extruder as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 is 120°C, Zone 3 to the die head is 130°C, and the screw speed is controlled at 300 rpm for asymmetric spatiotemporal gradient melt extrusion. (6) The extruded high-temperature melt is pressed into a sheet with a thickness of 1.5 mm by a pressing roller, and then cooled and shaped by a water-cooled fan before being crushed into small pieces by a crusher. (7) The sheet material is fed into an ACM micro pulverizer with an internal circulating water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. Then, the powder with a particle size D50 of 45μm is collected by cyclone separation and sieving to obtain the finished powder coating. Example
[0061] This embodiment provides a high-temperature resistant, insulating, and flame-retardant powder coating with an emphasis on electrical insulation properties, and its preparation method, including the following steps: (1) Weigh 45 kg of bisphenol A type solid epoxy resin, 20 kg of biphenyl type crystalline solid epoxy resin and 10 kg of solid methyl phenyl polysiloxane resin by weight, put them into a mixing tank and mix them to obtain material group A. (2) Weigh out 15 kg of calcium hypophosphate, 10 kg of zinc borate, 10 kg of phlogopite powder, 4 kg of polymeric aromatic carbodiimide, 3 kg of hydrophilic fumed silica, 8 kg of amino pre-expanded modified layered bimetallic hydroxide prepared in Preparation Example 1, 1.0 kg of leveling agent, 0.5 kg of degassing agent, 3.0 kg of dicyandiamide and 0.2 kg of 2-methylimidazole, and put them into a mixing tank for preliminary mixing to obtain material group B; (3) Put material group A and material group B into a high-speed mixer and mix at 800 rpm for 3 minutes to obtain a premix; (4) The premixed material is fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 40. The main feed port is located in the first zone of the extruder. At the same time, 1.0 kg of the catalyst masterbatch prepared in Preparation Example 4 is fed into the material group C independently and continuously through the side feeder located in the third zone of the extruder. (5) Set the temperature step parameters of the twin-screw extruder as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 is 115℃, Zone 3 to the die head is 125℃, and the screw speed is controlled at 300 rpm for asymmetric spatiotemporal gradient melt extrusion. (6) The extruded high-temperature melt is pressed into a sheet with a thickness of 1.5 mm by a pressing roller, and then cooled and shaped by a water-cooled fan before being crushed into small pieces by a crusher. (7) The sheet material is fed into an ACM micro pulverizer with an internal circulating water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. Then, the powder with a particle size D50 of 40μm is collected by cyclone separation and sieving to obtain the finished powder coating. Example
[0062] This embodiment provides a high-temperature resistant, insulating, and flame-retardant powder coating with an emphasis on extreme flame-retardant properties, and its preparation method, including the following steps: (1) Weigh 55 kg of bisphenol A type solid epoxy resin, 10 kg of biphenyl type crystalline solid epoxy resin and 15 kg of solid methyl phenyl polysiloxane resin by weight, put them into a mixing tank and mix them to obtain material group A. (2) Weigh out 25 kg of calcium hypophosphate, 20 kg of zinc borate, 5 kg of phlogopite powder, 4 kg of polymeric aromatic carbodiimide, 5 kg of hydrophilic fumed silica, 3 kg of amino pre-expanded modified layered bimetallic hydroxide prepared in Preparation Example 1, 1.0 kg of leveling agent, 0.5 kg of degassing agent, 4.0 kg of dicyandiamide and 0.4 kg of 2-methylimidazole, and put them into a mixing tank for preliminary mixing to obtain material group B; (3) Put material group A and material group B into a high-speed mixer and mix at 800 rpm for 3 minutes to obtain a premix; (4) The premixed material is fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 40. The main feed port is located in the first zone of the extruder. At the same time, 1.0 kg of the catalyst masterbatch prepared in Preparation Example 4 is fed into the material group C independently and continuously through the side feeder located in the third zone of the extruder. (5) Set the temperature step parameters of the twin-screw extruder as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 is 115℃, Zone 3 to the die head is 125℃, and the screw speed is controlled at 300 rpm for asymmetric spatiotemporal gradient melt extrusion. (6) The extruded high-temperature melt is pressed into a sheet with a thickness of 1.5 mm by a pressing roller, and then cooled and shaped by a water-cooled fan before being crushed into small pieces by a crusher. (7) The sheet material is fed into an ACM micro pulverizer with an internal circulating water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. Then, the powder with a particle size D50 of 40μm is collected by cyclone separation and sieving to obtain the finished powder coating.
[0063] Comparative Example 1: Compared with Example 1, the difference is that 15 kg of biphenyl-type crystalline solid epoxy resin in the formulation is replaced with an equal weight of bisphenol A-type solid epoxy resin, and all other aspects are the same.
[0064] Comparative Example 2: Compared with Example 1, the difference lies in process step (4). Instead of using the catalyst masterbatch obtained in Preparation Example 4, 1.0 kg of aluminum acetylacetonate, zinc stannate and bisphenol A type solid epoxy resin of equivalent weight in the catalyst masterbatch of Preparation Example 4 are added together with material group A and material group B into a high-speed mixer and mixed. All of them are fed into the main feed port of zone 1 of the extruder together, without using a side feeder. The rest are the same.
[0065] Comparative Example 3: Compared with Example 1, the difference is that 4 kg of polymeric aromatic carbodiimide in material group B is replaced with an equal weight of bisphenol A type solid epoxy resin, and all other aspects are the same.
[0066] Comparative Example 4: Compared with Example 1, the difference is that the hydrophilic fumed silica in material group B and the fumed silica carrier in the leveling agent are replaced with an equal weight of fumed silica that has undergone complete surface hydrophobication treatment and does not contain free silanol groups. The content of the effective component of polyacrylate in the leveling agent remains unchanged, and all other components are the same.
[0067] Comparative Example 5: Compared with Example 1, the difference is that the amino-pre-expanded modified layered bimetallic hydroxide in material group B is replaced with an equal weight of unmodified layered bimetallic hydroxide native powder, and all other aspects are the same.
[0068] Test Example 1: Experimental Description: The temperature-dependent complex viscosity and three-stage shear recovery behavior of powder coating samples were tested using a rotational rheometer to observe the effect of crystalline epoxy resin on the viscosity of the system and the thixotropic recovery characteristics of the system.
[0069] Experimental steps: The powder coating products prepared in Example 1, Comparative Example 1 and Comparative Example 4 were selected as test objects and pre-pressed into round samples with a diameter of 25 mm and a thickness of 1.2 mm on a flatbed press.
[0070] The test was conducted using a rotational rheometer equipped with an ambient temperature control chamber, with a 25mm parallel plate clamp and a test gap set to 1.0mm.
[0071] Variable temperature rheological tests were conducted, with the test mode set to oscillation mode, a fixed strain of 0.5%, and an angular frequency of 10 rad / s. The temperature scan range was set to 90℃ to 140℃, and the heating rate was 3℃ / min. The changes in complex viscosity with temperature were recorded.
[0072] Thixotropic recovery tests were conducted, with the isothermal test temperature set at 120℃ and a steady-state shear mode employed. In the first stage, a low shear rate of 0.1 s⁻¹ was applied and maintained for 60 seconds to obtain the initial structural viscosity. In the second stage, a high shear rate of 10 s⁻¹ was applied and maintained for 60 seconds to simulate the shear flow state of the material. In the third stage, the shear rate was restored to 0.1 s⁻¹ and maintained for 180 seconds, and the viscosity recovery process was recorded. The viscosity value was extracted 10 seconds after the recovery stage.
[0073] Each test subject underwent at least three parallel tests. The data in the table is the arithmetic mean of the parallel test results. Experimental data are shown in Table 1: Table 1: Test data of rheological and thixotropic recovery properties of samples under varying temperatures
[0074] To further characterize the structural recovery of the system after shear removal, the thixotropic recovery rate was calculated as "viscosity after 10 seconds of recovery / average viscosity in the initial stage × 100%". The thixotropic recovery rates of Example 1, Comparative Example 1, and Comparative Example 4 were approximately 88.2%, 84.5%, and 31.9%, respectively. These results indicate that under the test conditions, the system containing hydrophilic fumed silica exhibits a high viscosity recovery level in the low-shear recovery stage, suggesting a significant tendency for structural recovery.
[0075] According to Table 1 and Figure 2 According to the data, in the variable-temperature rheological test, the complex viscosity of Example 1 was 826.4 Pa·s at 100°C, which decreased to 148.7 Pa·s after heating to 115°C, and further decreased to 93.2 Pa·s at 130°C. Under the same test conditions, the complex viscosities of Comparative Example 1 at 100°C, 115°C, and 130°C were 1083.6 Pa·s, 647.3 Pa·s, and 315.8 Pa·s, respectively. Compared with Comparative Example 1, Example 1 showed a more significant viscosity decrease near 115°C. This phenomenon is related to the melt transformation of the biphenyl-type crystalline solid epoxy resin in Example 1 within this temperature range. The low-viscosity resin phase formed after melting is beneficial for improving the wetting and coating state of the resin on the inorganic components in the highly filled system, thereby reducing the apparent viscosity of the system. Meanwhile, since the biphenyl-type crystalline solid epoxy resin in Comparative Example 1 was replaced by an equal weight of bisphenol A-type solid epoxy resin, the epoxy group concentration, resin composition, and curing network formation process of the system may all change. Therefore, the above comparison results reflect the rheological differences under the combined effect of the melt viscosity reduction effect of crystalline epoxy resin and the change in resin composition.
[0076] In the three-stage shear recovery test, the average viscosity in the initial stage of Example 1 was 1341.2 Pa·s, and the average viscosity in the initial stage of Comparative Example 4 was 645.7 Pa·s. Upon entering the high-shear stage, the high-shear end viscosities of Example 1 and Comparative Example 4 decreased to 52.6 Pa·s and 48.9 Pa·s, respectively, indicating that both exhibited significant shear thinning behavior at higher shear rates. The shear rate recovered to 0.1 s⁻¹. -1 Subsequently, the viscosity of Example 1 recovered to 1182.9 Pa·s after 10 seconds of recovery, while the corresponding viscosity of Comparative Example 4 was 206.3 Pa·s. This result indicates that, under the same shear history, the low-shear viscosity recovery capability of Example 1 is significantly higher than that of Comparative Example 4.
[0077] Based on the analysis of formulation differences, Comparative Example 4, which used surface-hydrophobicated fumed silica without free silanol groups to replace the hydrophilic fumed silica and the fumed silica carrier in the leveling agent, showed a significant reduction in viscosity during the recovery phase. Without limiting the specific mechanism of action, it can be considered that a reversible physical interaction network may form between the silanol groups on the surface of the hydrophilic fumed silica in Example 1, the urea structure in the system, and the polar groups in the resin phase. This network contributes to viscosity recovery under low shear conditions. This type of structural recovery behavior can improve the melt's anti-sagging ability under static or low shear conditions, thereby helping the powder coating maintain the coating thickness at the substrate edge during thermosetting.
[0078] Test Example 2: Experimental Description: Fourier transform infrared spectroscopy was used to test the samples. By analyzing the changes in characteristic absorption peaks in specific wavenumber ranges, the interfacial chemical reaction between epoxy resin and polysiloxane in the system, as well as the addition conversion process between polymeric carbodiimide and water, were observed.
[0079] Experimental steps: The powder coating products prepared in Example 1, Comparative Example 2 and Comparative Example 3 were used as test subjects.
[0080] Each sample was placed in a vacuum drying oven and treated at 60°C for 4 hours to reduce the interference of physically adsorbed moisture on the sample surface on the test results.
[0081] Accurately weigh 2 mg of dried sample powder and 200 mg of dried and purified potassium bromide powder, place them in an agate mortar and grind them until they are evenly mixed.
[0082] The mixed powder was transferred to a tableting mold and pressed under 10 MPa pressure for 2 minutes to obtain a test sheet with uniform thickness and a semi-transparent appearance.
[0083] The compressed tablets were subjected to transmission scanning tests using a Fourier transform infrared spectroscopy (FTIR) instrument. The scanning wavenumber range was set to 4000 cm⁻¹. -1 Up to 400cm -1 Spectral resolution of 4 cm -1 Each sample was scanned a total of 32 times.
[0084] After the test was completed, the original spectrum was baseline-calibrated and smoothed using instrument analysis software, and absorbance values in specific wavenumber ranges were extracted for comparative analysis.
[0085] Each test subject underwent at least three parallel tests. The data in the table is the arithmetic mean of the parallel test results. Experimental data are shown in Table 2: Table 2: Absorbance test data of characteristic peaks in infrared spectrum of samples
[0086] According to the data in Table 2, at 1085cm -1 In the nearby wavenumber range, the absorbance of Example 1 was 0.452, higher than that of Comparative Example 2 (0.126). Absorption in this wavenumber range is typically related to silicon-oxygen bond-related vibrations such as Si-O-Si and Si-OC. Under the test conditions, the enhanced absorption in this region of Example 1 indicates a relatively high degree of formation or rearrangement of silicon-oxygen bond-related structures in its system. In Comparative Example 2, the catalyst and all components were added together from the main feed inlet, and its absorbance at 1085 cm⁻¹... -1The low absorption intensity in the vicinity indicates that different catalyst addition methods may affect the interfacial interaction state between the epoxy resin phase, the silicone resin phase, and the inorganic components. These results suggest that side-feeding is beneficial for forming a more complete interfacial reaction or interfacial compatibility structure during extrusion processing.
[0087] At 1648cm -1 In the nearby wavenumber range, the absorbance of Example 1 and Comparative Example 2 were 0.387 and 0.365, respectively, both significantly higher than that of Comparative Example 3 (0.034). This absorption can be attributed to urea carbonyl-related absorption. Since Comparative Example 3 did not contain a polymeric aromatic carbodiimide, its absorption in this region was low; while Examples 1 and Comparative Example 2 both contained polymeric aromatic carbodiimide and exhibited high absorption in this region, indicating that the carbodiimide group may react with trace amounts of moisture or other active components in the system during processing or subsequent treatment, generating products containing urea structures.
[0088] At 2135cm -1 In the nearby wavenumber range, this absorption peak corresponds to the characteristic absorption of the carbodiimide group (-N=C=N-). The absorbance in this region for Example 1 and Comparative Example 2 are 0.012 and 0.015, respectively, both at low levels; Comparative Example 3, due to the absence of a polymerized aromatic carbodiimide, also exhibits a low corresponding absorption. (Combined with 1648 cm⁻¹) -1 The absorption changes in the vicinity suggest that in the system containing polymeric aromatic carbodiimide, some carbodiimide groups may participate in moisture capture or related addition reactions. It should be noted that because the powder coating system contains resin, inorganic fillers, and various additives, infrared absorption peaks may overlap, scatter, and be affected by baseline. Therefore, the above peak intensity changes are mainly used to illustrate the relative trends between different samples and are not intended to limit specific reaction conversion rates.
[0089] Based on the results in Table 2, Example 1 was performed at 1085 cm⁻¹. -1 It exhibits high silicon-oxygen bond-related absorption in the vicinity, and at 1648 cm⁻¹ -1 The surrounding area exhibits significant urea carbonyl-related absorption. This result suggests a possible synergistic effect between the side-feed catalytic process, the polymeric aromatic carbodiimide, and the silanol-containing component in Example 1, resulting in good interfacial compatibility and a certain degree of moisture capture and conversion during processing. This effect helps reduce the likelihood of pore formation due to trace moisture evaporation during subsequent high-temperature curing and contributes to the physical network construction of the melt.
[0090] Test Example 3: Experimental Description: The edge coverage of the powder coating on a specific conductive substrate and the electrical breakdown strength of the system were tested to observe the rheological control effect of the coating during the baking and curing process, as well as the insulation performance of the coating after curing in suppressing electrical treeing degradation.
[0091] Experimental steps: The powder coating products prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were selected as test objects.
[0092] Prepare several pure copper busbars with a cross-sectional dimension of 30mm x 3mm, and machine all four edges into rounded corners with a chamfer radius of 1.0mm. Use electrostatic spraying equipment to evenly spray each group of powder coating onto the surface of the copper busbars.
[0093] The coated copper busbar was placed in an oven at 180°C for 20 minutes to cure. After cooling to room temperature, it was cut along the length of the copper busbar and the cross-section was ground and polished.
[0094] The coating thickness in the planar area and the thinnest coating thickness in the four rounded corner areas were measured under a metallographic microscope. The percentage of the average rounded corner thickness to the average planar thickness was calculated as the edge coverage of the sample.
[0095] Following standard testing methods for the electrical strength of insulating materials, a smooth, cured sample with a thickness of 1.0 mm was prepared using powder coating. The sample was placed in a test tank filled with insulating oil, and tested using a high-voltage breakdown voltage tester. A power frequency AC voltage was applied uniformly at a rate of 2.0 kV / s until the sample broke down. The voltage value at the moment of breakdown was recorded, and the electrical breakdown strength of each sample was calculated.
[0096] Each test subject underwent at least three parallel tests. The data in the table is the arithmetic mean of the parallel test results. Experimental data are shown in Table 3: Table 3: Sample Edge Coverage and Electrical Breakdown Strength Test Data
[0097] According to the data in Table 3, the edge coverage rates of Examples 1 to 5 were 45.2%–51.4%, higher than the 16.8% of Comparative Example 4. In Comparative Example 4, after replacing the hydrophilic fumed silica and the fumed silica carrier in the leveling agent with fumed silica that had undergone surface hydrophobication treatment and did not contain free silanol groups, the edge coverage rate was significantly reduced. The above results indicate that under the test conditions, the introduction of hydrophilic fumed silica helps to improve the thickness retention ability of the powder coating in the rounded corner area of the copper busbar.
[0098] Combining the rheological results from Test Example 1, it can be seen that the system in the example exhibits a high viscosity recovery level during the low-shear recovery stage. Without specifying the exact mechanism, it can be assumed that a reversible physical interaction network may form between the silanol groups on the surface of the hydrophilic fumed silica, the urea structure in the system, and the polar groups in the resin phase, allowing the coating melt to maintain high structural strength under static or low-shear conditions. This structural state helps reduce the tendency of the coating to flow at the substrate edges during thermosetting, thus allowing the coating to retain a certain thickness in the rounded corner areas. Meanwhile, the biphenyl-type crystalline solid epoxy resin, the dispersion state of the inorganic fillers, and the viscoelastic changes during the curing process in the example system may also affect the edge coverage; therefore, this performance improvement can be understood as the result of the combined effect of multiple formulation factors.
[0099] In the electrical breakdown strength test, the electrical breakdown strengths of Examples 1 to 5 ranged from 39.8 kV / mm to 46.7 kV / mm, which were higher than those of Comparative Example 3 (22.6 kV / mm) and Comparative Example 5 (25.3 kV / mm). Comparative Example 3 did not contain polymeric aromatic carbodiimide, resulting in a lower electrical breakdown strength; in Comparative Example 5, replacing the amino-pre-expanded modified layered bimetallic hydroxide with unmodified virgin layered bimetallic hydroxide powder also resulted in a lower electrical breakdown strength. These results indicate that both polymeric aromatic carbodiimide and amino-pre-expanded modified layered bimetallic hydroxide have a positive impact on improving the insulation performance of the coating.
[0100] For polymeric aromatic carbodiimides, they can undergo addition reactions with trace amounts of moisture or other active components in the system, thereby reducing the possibility of micropores formed during curing due to moisture evaporation. Since micropores, bubbles, or interface defects can lead to localized electric field concentration and reduce the coating's voltage withstand capability, reducing these defects is beneficial for improving the electrical breakdown strength of the cured coating. For amino-pre-expanded modified layered bimetallic hydroxides, aminosilane treatment helps improve their compatibility and dispersion with the resin system, making it easier for the layered structure to form a dispersed inorganic barrier phase in the matrix. This type of inorganic layered structure may block, deflect, or prolong local charge migration and discharge path extension, thereby helping to improve the overall insulation performance of the material.
[0101] The combined results of edge coverage and electrical breakdown strength tests show that the system in this example exhibits superior coating retention in the rounded corner area of the copper busbar and excellent electrical insulation performance of the cured coating. This result demonstrates that the combined use of crystalline epoxy resin, hydrophilic fumed silica, polymeric aromatic carbodiimide, and amino-pre-expanded modified layered bimetallic hydroxide can, to a certain extent, balance the edge coverage and electrical insulation performance of powder coatings.
[0102] Test Example 4: Experimental Description: The thermal degradation behavior of the powder coating system under high temperature and its flame retardant properties after curing were tested to observe the ceramic and char state of the system when heated, as well as its effect on preventing the spread of combustion and the generation of molten droplets when in contact with flame.
[0103] Experimental steps: The powder coating products prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were selected as test objects.
[0104] The powder coating was molded and cured at 180°C using a flat vulcanizing machine. Standard specimens for vertical combustion test with dimensions of 130mm x 13mm x 3.2mm and for limiting oxygen index test with dimensions of 120mm x 10mm x 4mm were prepared. An appropriate amount of uncured powder coating sample was also ground into powder in a mortar for later use.
[0105] High-temperature thermal stability was tested using a thermogravimetric analyzer. 5 to 8 mg of powder sample was weighed and placed in an alumina crucible. The temperature was programmed under a nitrogen atmosphere with a gas flow rate of 50 mL / min. The temperature scan range was set from 30 °C to 800 °C, and the heating rate was 10 °C / min. The mass change of the sample with temperature was recorded, and the char residue at 800 °C was extracted.
[0106] According to the standard method for vertical burning test, the sample is vertically fixed on the bracket inside the combustion chamber, and the lower end of the sample is ignited using a standard Bunsen burner flame. The flaming time and flameless burning time of the sample are recorded after the flame is removed. It is observed and recorded whether molten droplets fall during the burning process and whether the degreased cotton at the bottom is ignited. The single flaming time, total flaming time, flameless burning time and whether the burning reaches the fixture position are counted for each group of samples. The flame retardancy rating of the sample is determined according to the standard.
[0107] The limiting oxygen index (LOI) was used for testing. The sample was vertically fixed inside the combustion chamber, the oxygen and nitrogen flow rates in the mixed gas were adjusted, the top of the sample was ignited, and the minimum oxygen volume percentage required to maintain stable combustion for 3 minutes or to achieve a combustion length of 50 mm was recorded.
[0108] In thermogravimetric analysis and limiting oxygen index (LOI) testing, each test subject underwent at least three parallel tests. The char residue and LIO data in the table are the arithmetic mean of the parallel test results. In the UL94 vertical combustion test, at least five spline samples were used for grading each test subject group. The experimental data are shown in Table 4. Table 4: Test data on thermal stability and flame retardant properties of samples
[0109] According to the data in Table 4, in the thermal stability test, the char residue of Examples 1 to 5 at 800℃ was 44.2%–56.1%, higher than that of Comparative Example 5 (29.8%). In Comparative Example 5, after replacing the amino-pre-expanded modified layered bimetallic hydroxide with unmodified virgin layered bimetallic hydroxide powder, the char residue at 800℃ was significantly reduced. These results indicate that under the test conditions, the introduction of amino-pre-expanded modified layered bimetallic hydroxide helps improve the residue and thermal stability of the powder coating system under high-temperature conditions.
[0110] Based on the formulation analysis, the amino-pre-expanded modified layered bimetallic hydroxide, after silane treatment, may exhibit better resin compatibility and dispersion. Its layered structure can participate in the construction of the carbon layer structure as an inorganic barrier phase during heating. Simultaneously, components such as calcium hypophosphite, zinc borate, phlogopite powder, fumed silica, and organosilicon resin in the system may also jointly participate in the formation of high-temperature char and the inorganic barrier layer. The synergistic effect of these multiple components is beneficial for forming a relatively continuous carbon-inorganic composite barrier structure during the thermal decomposition of the material, thereby reducing the degree of further thermal decomposition and volatilization of the underlying resin. In Comparative Example 5, the unmodified layered bimetallic hydroxide may have weaker compatibility and dispersion with the resin system; therefore, its contribution to the integrity of the carbon layer structure is relatively limited, manifested as a reduced char rate.
[0111] In the flame retardant performance test, Examples 1 to 5 all achieved the UL94 V-0 rating, and no dripping phenomenon was observed, with limiting oxygen indices ranging from 33.6% to 41.2%. Specifically, Example 5 had a limiting oxygen index of 41.2% and a char residue of 56.1% at 800°C, indicating that increasing the content of the flame retardant component and adjusting the inorganic filler ratio resulted in a high level of flame retardancy. In contrast, Comparative Examples 1, 2, 4, and 5 showed varying degrees of decrease in flame retardancy or dripping, suggesting that factors such as the biphenyl-type crystalline solid epoxy resin, the catalyst addition method, the hydrophilic fumed silica, and the modified layered bimetallic hydroxide can all affect the flame retardant performance of the system.
[0112] In Comparative Example 2, the catalyst masterbatch side feeding method was not used. Instead, the catalyst component was added together with other materials through the main feed port. Its limiting oxygen index was 27.5%, its UL94 flame retardancy rating was V-2, and it exhibited molten droplet phenomena that ignited cotton. Based on the analysis of the preparation process, premature introduction of the catalyst into the extrusion system may cause localized reactions to occur earlier or localized viscosity to increase, thereby affecting the mixing uniformity between the resin phase, organosilicon phase, and inorganic components. This difference may further affect the phase uniformity of the cured product and the continuity of the char layer or inorganic barrier layer during heating, ultimately leading to a decrease in flame retardant performance.
[0113] In Comparative Example 4, after replacing the hydrophilic fumed silica and the fumed silica carrier in the leveling agent with fumed silica that had undergone surface hydrophobication treatment and contained no free silanol groups, the limiting oxygen index was 29.4%, the flame retardancy rating was V-1, and molten droplets that did not ignite cotton were observed. This result indicates that the silanol structure on the surface of the hydrophilic fumed silica may help enhance the internal physical interaction network and char layer support effect of the system, thus positively impacting the suppression of melt dripping and the maintenance of the flame retardant layer integrity.
[0114] The combined results of thermal stability, limiting oxygen index, and UL94 vertical burning tests show that the system in this example exhibits superior performance in terms of high-temperature char residue, oxygen index, and anti-dripping properties. These results indicate that the combined use of silicone resin, phosphorus-containing flame-retardant components, zinc borate, hydrophilic fumed silica, phlogopite powder, and amino-pre-expanded modified layered bimetallic hydroxide can improve the thermal stability and flame-retardant properties of the cured powder coating to a certain extent. Furthermore, controlling the addition position of the catalytic components through a catalyst masterbatch-side feeding method is beneficial for improving the component distribution during the system processing and further enhancing the flame-retardant performance of the cured coating.
[0115] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-temperature resistant, insulating, and flame-retardant powder coating, characterized in that, The powder coating is made from raw materials comprising the following parts by weight: Bisphenol A type solid epoxy resin: 40-60 parts; Biphenyl-type crystalline solid epoxy resin: 10-20 parts; Solid methylphenyl polysiloxane resin: 5-15 parts; Calcium hypophosphate: 15-25 parts; Zinc borate: 10-20 parts; Phlogopite powder: 5-15 parts; Polymerized aromatic carbodiimide: 2-6 parts; Hydrophilic fumed silica: 1-5 parts; Amino-pre-expanded modified layered bimetallic hydroxide: 3-8 parts; Leveling agent: 0.5–1.5 parts; Degassing agent: 0.2–1.0 parts; Dicyandiamide: 2.0–5.0 parts; 2-Methylimidazole: 0.1–0.5 parts; Catalyst masterbatch: 0.5 to 1.5 parts.
2. The high-temperature resistant, insulating, and flame-retardant powder coating according to claim 1, characterized in that, The parameters of the raw materials satisfy: The bisphenol A type solid epoxy resin is end-capped with epoxy groups at both ends, with an epoxy equivalent of 700-900 g / eq and a softening point of 85-95℃. The biphenyl-type crystalline solid epoxy resin is 3,3',5,5'-tetramethyl-4,4'-biphenyl diglycidyl ether, with an epoxy equivalent of 180-200 g / eq, a crystallization melting point of 100-110℃, and a melt viscosity of ≤0.05 Pa·s at 120℃. The solid methylphenyl polysiloxane resin is a cross-linked organosilicon resin with Si-O-Si bonds as the backbone and phenyl and methyl side groups, with a silanol mass fraction of 2% to 6% and a softening point of 90 to 105°C.
3. The high-temperature resistant, insulating, and flame-retardant powder coating according to claim 1, characterized in that, The parameters of the raw materials satisfy: The polymeric aromatic carbodiimide is a high molecular weight polymer with -N=C=N- functional groups and sterically hindered aryl structures in the main chain repeating unit, with a residual isocyanate group mass fraction ≤0.1% and a softening point of 70-90℃. The hydrophilic fumed silica is an amorphous fumed silica nanoparticle that has not undergone surface hydrophobication treatment, with a specific surface area of 200–300 m². 2 / g; The leveling agent is a polyacrylate copolymer with a weight-average molecular weight range of 3,000 to 10,000, formed by the physical adsorption of 65% polyacrylate onto a 35% fumed silica carrier.
4. The high-temperature resistant, insulating, and flame-retardant powder coating according to claim 1, characterized in that, The amino-pre-expanded modified layered bimetallic hydroxide is prepared by a method comprising the following steps: Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were dissolved in deionized water at a magnesium ion to aluminum ion molar ratio of 2:1 to 3:1 to prepare a mixed salt solution. The mixed salt solution was added dropwise to an alkaline precipitate containing sodium hydroxide and sodium carbonate, maintaining the pH of the system at 9.5–10.0, and crystallized and aged at 70–90°C for 12–24 hours. After washing and drying, the original powder was obtained. The virgin powder was dispersed in a mixed solvent of anhydrous ethanol and water in a volume ratio of 9:1, and 3-aminopropyltriethoxysilane was added at a mass of 5% to 10% of the virgin powder. The mixture was refluxed at 70 to 90°C for 6 to 8 hours. After separation and drying, the amino-pre-expanded modified layered bimetallic hydroxide was obtained.
5. The high-temperature resistant, insulating, and flame-retardant powder coating according to claim 1, characterized in that, The catalyst masterbatch is produced by melt extrusion of the following raw materials in parts by weight: Aluminum acetylacetone: 20-80 parts; Zinc stannate: 200-500 parts; Bisphenol A type solid epoxy resin: 300-500 parts.
6. A method for preparing a high-temperature resistant, insulating, and flame-retardant powder coating as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Weigh out bisphenol A type solid epoxy resin, biphenyl type crystalline solid epoxy resin and solid methylphenyl polysiloxane resin according to the formula, and mix them to obtain material group A; S2. Weigh the following according to the formula: calcium hypophosphate, zinc borate, phlogopite powder, polymeric aromatic carbodiimide, hydrophilic fumed silica, amino pre-expanded modified layered bimetallic hydroxide, leveling agent, degassing agent, dicyandiamide and 2-methylimidazole, and mix them to obtain material group B. S3. Add material group A and material group B together into a mixer and mix to obtain a premix; S4. The premixed material is continuously fed into the main feed port of the twin-screw extruder; at the same time, the catalyst masterbatch weighed according to the formula is independently and continuously fed into the twin-screw extruder through the side feeder. S5. Set the temperature step parameters and screw speed of the twin-screw extruder, and perform melt extrusion; S6. Press the extruded high-temperature melt into thin sheets, cool and shape it, and then crush it into sheet material; S7. The sheet material is fed into a pulverizer for pulverization, and the powder of the target particle size is collected by sieving to obtain the powder coating.
7. The method for preparing powder coating according to claim 6, characterized in that, In step S4, the main feed port of the twin-screw extruder is located in zone 1 of the twin-screw extruder, and the side feeder is located in zone 3 of the twin-screw extruder; in step S5, the screw speed of the twin-screw extruder is controlled to be 300 rpm.
8. The method for preparing powder coating according to claim 6, characterized in that, In step S5, the barrel operating temperature step parameters of the twin-screw extruder are set as follows: Zone 1 is kept at room temperature and water-cooled, Zone 2 has an operating temperature of 110-120°C, and Zone 3 to the die head has an operating temperature of 120-130°C.
9. The method for preparing powder coating according to claim 6, characterized in that, In step S7, the sheet material is fed into a pulverizer equipped with a water cooling system for pulverization. The temperature of the pulverizing chamber is controlled to not exceed 30°C. After sieving, powder with a particle size D50 of 35-45 μm is collected.
10. The method for preparing powder coating according to claim 6, characterized in that, Before performing step S4, the catalyst masterbatch is prepared as follows: Aluminum acetylacetone, zinc stannate, and bisphenol A type solid epoxy resin are added to a mixer and mixed to obtain a masterbatch premix. The masterbatch premix is fed into a twin-screw extruder, and the barrel operating temperature is set to 85-100℃ for melt extrusion. After the extruded material is cooled and shaped, it is cut into particles with a diameter of 2-3 mm to obtain the catalyst masterbatch.